Humane Papillomviren bei Plattenepithelkarzinomen der Kopf- und Halsregion: Relevanz für Prognose, Therapie und Prophylaxe - Reuschenbach, Miriam; Prigge, Elena-Sophie; Sauer, Madeleine; Knebel Doeberitz, Magnus von (HNO, 2016)
Human papilloma viruses (HPV) are responsible for approximately half of all oropharyngeal squamous cell carcinomas (OPSCC) and incidence rates of HPV-associated OPSCC continue to increase substantially. The defined viral carcinogenesis permits development of specific diagnostic, therapeutic, and prophylactic approaches. Laboratory identification of HPV-associated OPSCC may be achieved by p16INK4a immunohistochemistry combined with HPV DNA detection by polymerase chain reaction (PCR) using tumor tissue. Patients with HPV-associated OPSCC have a relatively good prognosis; therefore, the HPV status plays an important role in patient guidance. Due to the relatively favorable prognosis, ongoing studies are evaluating whether less rigorous therapy for HPV-positive patients results in equally good cure rates. The criteria for patient selection are, however, still uncertain. Particularly markers for detection of HPV-positive patients with a high risk of treatment failure are lacking. Besides tumor stage and comorbidities, distinct genomic, epigenetic, and immunologic alterations are prognostically relevant for HPV-associated OPSCC, and might be of predictive value. Furthermore, the characteristic molecular alterations suggest the possibility of novel vigilant and specific therapy approaches. These may be inhibitors of the phosphatidylinositol 3‑kinase (PI3K) pathway, which is frequently activated in HPV-associated OPSCC, and immunotherapeutic methods, e. g., therapeutic vaccination. Although prophylactic HPV vaccinations may also prevent development of HPV-associated OPSCC, foreseeable effects on OPSCC incidence will be low, given the low vaccination rates in Germany. This highlights the fact that interdisciplinary research networks should enhance the necessary activities related to HPV-associated OPSCC.
Gesehen am 31.01.2018